Prevalence of in‐hospital nonsteroidal antiinflammatory drug exposure in patients with a primary diagnosis of heart failure. Issue 3 (June 2017) - Alvarez, Paulino A.; Putney, David; Ogunti, Richard; Puppala, Mamta; Ganduglia, Cecilia; Torre‐Amione, Guillermo; Schutt, Robert; Wong, Stephen T. C.; Estep, Jerry D.
Summary: Aim: To determine the prevalence of in‐hospital nonsteroidal antiinflammatory drug (NSAID) exposure and associated outcomes in patients admitted with a primary diagnosis of heart failure. Methods: We performed a propensity‐matched cohort analysis of patients admitted to Houston Methodist Hospital System with a primary diagnosis of heart failure according to the International Classification of Diseases‐9‐Clinical Modification (ICD‐9‐CM) from January 1, 2011 to December 31, 2014. Results: Of the 9742 patients admitted with a primary diagnosis of heart failure, 384 patients (3.9%) were exposed to NSAID. After applying propensity scores we matched 305 NSAID exposed with 915 unexposed patients. Patients with in‐hospital NSAID exposure had a longer length of stay (7.0±8.8 days vs 6.1±8.5; P =.003) and increased prevalence of worsening renal function (34.4% vs 27.9%; P =.030). There were not statically significant differences in in‐hospital mortality rate or 30‐day all‐cause readmission rate. Conclusion: Exposure to NSAID in patients admitted with a primary diagnosis of heart failure was low but was associated with adverse outcomes including longer length of stay and higher prevalence or worsening renal function.